Outcome of COVID-19 Patients Receiving 6mg vs 12mg Dexamethasone at a Tertiary Care Hospital in Pakistan - Bari, Saba; Naseem, Arshad; Khan, Asad Zaman; Sajjad, Kaswar; Ali, Muhammad; Shehzad, Farrukh (Pakistan Armed Forces Medical Journal, 2022)
Objective: To compare the outcome in COVID 19 patients on oxygen managed with 6mg and 12 mg Dexamethasone at Pak Emirates Military Hospital Rawalpindi. Study Design: Comparative cross-sectional study. Place and Duration of Study: Pak Emirates Military Hospital Rawalpindi Pakistan, from Aug 2020 to Aug 2021. Methodology: Patients diagnosed with COVID-19 on PCR and were oxygen-dependent but not mechanical ventilation dependent were included in the study. They were randomly divided into two groups. Group-I received 6mg Dexamethasone, while Group-II received 12 mg Dexamethasone for ten days. They were followed up for 30 days to look for the outcome (prolonged admission, high dependency unit admission, intensive care admission, death). The difference in outcome in both groups was studied using the Pearson chi-square test. Results: Out of 600 patients included in the study, 401 (66.8%) were male, while 199 (33.2%) were female. The mean age of the study participants was 47.81 ± 8.716 years. 306 (51%) were given 6mg of Dexamethasone for ten days, while 294 (49%) were given 12mg of Dexamethasone for a similar time. prolonged admission (p-value-0.178), high dependency unit admission (pvalue-0.409), intensive care admission (p-value-0.176) and mortality (p-value-0.588) were not statistically significantly different in both the groups. Conclusion: All the outcome variables, including mortality and admission to the critical care unit, were not statistically significant in groups taking 6mg or 12 mg of Dexamethasone, so it could be concluded that a high dose of this medication is not superior in terms of efficacy when compared to the low dose.